Zinc(II), cobalt(II) and manganese(II) networks with phosphoserine ligand: Synthesis, crystal structures magnetic and conduction properties - Vallejo, J.; Salcedo, Inés R.; Pérez-Colodrero, Rosario Mercedes; Cabeza-Díaz, Aurelio; Świtlicka, A.; Cano, J.; Viciano-Chumillas, María (The Royal Society of Chemistry, 2017)
A series of zinc(II), cobalt(II) and manganese(II) coordination networks with the phosphoserine ligand (Pser) is synthesized and characterized. Whereas in compounds 1 and 2 with the general formula [M(Pser)]n [M = Zn (1) and Co(2)], the metal(II) ion presents a tetrahedral geometry, in [Co(Pser)(H2O)2]n (3) and [Mn(Pser)(H2O)]n (4)], the metal(II) ions are in a distorted octahedral geometry. The 3D frameworks are formed by inorganic layers built up from MO4 or MO6 polyhedra and phosphate groups. These layers are linked by the carboxylate groups of the phosphoserine ligand. The presence of extended hydrogen bonding stabilizes the 3D network and favors the proton transfer leading to moderate proton conductors. The highest proton conductivity, 2.70·10−5 S cm−1 (at 80 ºC and 95% RH), is obtained for compound 3. Temperature dependent magnetic susceptibility measurements for 2−4 reveal predominant antiferromagnetic interactions between the paramagnetic metal(II) ions.
Keywords: Fósforo - Compuestos; Conductividad eléctrica; Catalizadores; Pilas de combustible; Metal phosphoserine; Proton-conductivity